2012
DOI: 10.1590/s1981-67232012005000019
|View full text |Cite
|
Sign up to set email alerts
|

Production and action of an Aspergillus phoenicis enzymatic pool using different carbon sources

Abstract: Aspergillus phoenicis is an interesting heat tolerant fungus that can synthesize enzymes with several applications in the food industry due to its great hydrolytic potential. In this work, the fungus produced high enzymatic levels when cultivated on inexpensive culture media consisting of flakes from different origins such as cassava flour, wheat fibre, crushed soybean, agro-industrial wastes, starch, glucose or maltose. Several enzymatic systems were produced from these carbon sources, but amylase was the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Pasin et al (2014) reported high levels of amylase activity in A. japonicus when cultivated in different agro-industrial residues. The presence of this activity in the cultures might be due to the fact that amylases are constitutive enzymes, which are generally located in the fungal cell walls (Benassi et al 2012).…”
Section: Enzymesmentioning
confidence: 99%
“…Pasin et al (2014) reported high levels of amylase activity in A. japonicus when cultivated in different agro-industrial residues. The presence of this activity in the cultures might be due to the fact that amylases are constitutive enzymes, which are generally located in the fungal cell walls (Benassi et al 2012).…”
Section: Enzymesmentioning
confidence: 99%
“…Essential oils (EOs), which are extracted from aromatic plants, have been widely studied in the food and pharmaceutical fields not only because they are natural GRAS products but also due to their various bioactive properties such as antioxidant, antimicrobial, anti-tumor, and anti-inflammatory [15][16][17]. Several studies have reported the incorporation of EOs in food packaging, which showed the efficiency against microorganisms and oxidants and the benefits on food preservation [18][19][20]. The essential oil of Angelica sinensis (Oliv.)…”
Section: Introductionmentioning
confidence: 99%
“…The second-most frequently identified Aspergillus genus in the WSP was Aspergillus phoenicis. This is an interesting heat-tolerant fungus that can synthesize enzymes and has several applications in the food industry due to its great hydrolytic potential [55]. This may explain its prevalence in the household waste of the analysed WSP.…”
Section: Identification Of Fungal Aerosolmentioning
confidence: 99%